2006
DOI: 10.1038/sj.ijir.3901445
|View full text |Cite
|
Sign up to set email alerts
|

Do motorcyclists have erectile dysfunction? A preliminary study

Abstract: The aim of the present study was to evaluate the relationship between motorcycling and erectile dysfunction (ED). We investigated the relationship between motorcycling and erectile function using the 5-items version of the International Index of Erectile Function (IIEF5) in 234 motorcyclists (response rate 75%) and 752 healthy controls (response rate 66%). In all, 161 (69%) of 234 motorcyclists were diagnosed as ED based on IIEF5. The prevalence of ED in the motorcycle group increased by age as: 58, 63, 76 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…6 In the previous study, logistic regression analysis showed that motorcycling was an independent risk factor for ED. In this study, we found that LUTS was also a ED and LUTS in Japanese motorcyclists Y Naya et al risk factor for ED in motorcyclists.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…6 In the previous study, logistic regression analysis showed that motorcycling was an independent risk factor for ED. In this study, we found that LUTS was also a ED and LUTS in Japanese motorcyclists Y Naya et al risk factor for ED in motorcyclists.…”
Section: Discussionmentioning
confidence: 91%
“…In our previous study, vibration seemed to be related with the cause of ED in motorcyclists. 6 The vibrational energy causes extracellular signal-regulated kinase activation and endothelin-1 production. 16 In ED patients, plasma levels of endothelin-1 are elevated and associated with reduction of the growth hormone, NO and cGMP in the systematic and cavernous blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Hippocrates attributed these problems to the long time spent in the saddle and a habit of cutting a vein behind the ear "to cut which causes impotence. " 9,10 Curiously, more modern research demonstrates that horseback riding does not appear to be linked to ED, 8 but motorcycling or the "iron horse" may be.…”
mentioning
confidence: 99%